The Effect of Using Digital Technology on the Selling Power of MSMEs Products After the Covid-19 Pandemic at Klambir V Kebun Village - Ahmad Fadlan; Yusuf, Mohammad; Pernanda, Herurel (Best Journal of Administration and Management, 2023)
This study aims to determine the effect of the use of digital technology on the selling power of MSMEs products after the Covid-19 pandemic in Klambir V Kebun Village, Hamparan Perak District, Deli Serdang Regency. The type of research used is explanatory research which describes or explains a generalization of the sample to the population, which uses samples and hypotheses to test the hypothesis using inferential statistics. The findings show that the factors that most influence the use of digital technology on the selling power of MSMEs products after the Covid-19 pandemic in Klambir V Kebun Village are production variables, capital variables, and the technology variable itself. Based on multiple linear regression analysis, it shows that production, capital, and technology have a significant effect on the competitiveness and development of MSMEs productivity.